Integrated management systems for the improvement of the physical-hydric quality of a cerrado oxisol - Barros, Leonardo Rodrigues; Ribon, Adriana Aparecida; Fernandes, Kathleen Lourenço; Sousa, Jéssika Lorrine de Oliveira; Correchel, Vladia; Backes, Clarice; Santos, Alessandro José Marques; Alves, Amanda Romeiro (Southern Cross Publishing, 2018)
Degradation of the physical-hydric quality of the soils is one of the great obstacles to agricultural production in this country. Inadequate pasture management is one of the main factors that promote soil degradation, by contrast, some alternative farming practices have emerged. The objective of this work was to study the water retention curve obtained through the Richards chamber method, among other attributes of a Yellow Oxisol under Cerrado, planted with pastures in different integrated management systems: integrated crop-livestock-forestry (ILPF); integrated livestock-forestry (IPF); crop-livestock farming (ILP); Unmanaged pasture (P); Rotated picket (PIQ), and native forest (MN). Attributes such as water retention curve, soil density, macro, microporosity and total porosity, available water capacity and organic matter were evaluated in four soil layers (0 - 0.10 m, - 0.20 m, - 0.30 Me - 0.40 m). It was observed that the water content, given by the water retention curve in the soil, was higher in all layers of the IPF treatment. The results of the other evaluated attributes revealed that integrated management systems have potential to improve the physical and hydric conditions of the soil.
Keywords: Soil conservation systems; Soil physical quality; Soil pore system; Water availability